Spontaneous aortocaval fistula presenting with acute liver and renal failure: A case report - Mehmet KANBAY; Gürden GÜR; Fatih BOYVAT; Atılay TAŞDELEN; Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-